The School Teachers’ Creativity and Self-efficacy in Writing an Academic Text: A Rasch-Based Survey Analysis - Mulyono, Herri (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
The present study aimed to examine the academic writing creativity and self-efficacy of Indonesian school teachers. Under a survey design, a five-point Likert scale of Academic Writing Creativity and Self-Efficacy (ACSE) questionnaire was distributed to school teachers in Jakarta, Bogor, Depok, Tangerang, and Bekasi, of whom 262 voluntarily completed it. Rasch analysis was conducted on the quantitative data, with the results showing that almost half of Indonesian school teachers possess a low level of academic writing creativity and self-efficacy (N = 112, or 48.7%), some with a moderate level (N = 88, or 38.3%), and a few with a high level (N = 30, or 13%). Although teachers were found to have a strong ability to seek feedback on their writing from their colleagues and to make decisions about whether to accept or reject it, they lacked creativity in their academic writing, particularly their skill to express original ideas using a wide range of words and expressions in a grammatically correct manner. Moreover, their competence in utilizing technology for writing resources and assistance, such as researching pertinent literature, referencing accurately, paraphrasing effectively, and addressing spelling and other language errors, was limited. A discussion of the findings was presented in the article, and recommendations were offered regarding further academic writing training and research.